Resource logics with a diminishing resource: extended abstract - Alechina, Natasha; Logan, Brian (2018)
Model-checking resource logics with production and consumption of resources is a computationally hard and often undecidable problem. We show that it is more feasible under the assumption that there is at least one diminishing resource, that is, a resource which is consumed by every action.